Being chimaera: a monstrous identity for SoTL academics - Bennett, Rebecca; Hobson, Julia; Jones, Angela; Martin-Lynch, Pamela; Scutt, Cecily; Strehlow, Karin; Veitch, Sarah (Taylor & Francis, 2015)
Lurking on the fringes of university culture are academic identities that do not fit into the usual disciplinary communities. Aiming to explore the experience of ‘being academic’ when not linked directly to a discipline, this paper examines the stories of a diverse group of SoTL scholars who work in a centralised multi-campus academic skills support centre in an Australian university. Framed as group auto-ethnography, the paper inquires into the everyday experience of these academics through narrative analysis of multiple first-person accounts and makes apparent the monstrousness of de-affiliated academic identities. Despite diverse disciplinary backgrounds, the author-participants found that they now shared a tripartite academic identity formed through the negotiation of three roles: the teacher, the disciplinarian, and the educational researcher. Using the chimaera, a mythical three-headed monster as an organising metaphor, this paper aims to provide agency and visibility for often under-represented and unacknowledged academic identities.